The Effect Of Particle Size On The Characterization Of Activated Carbon From Tropical Black Bamboo (Gigantochloa Atroviolacea) - Envrinda Arief Fauzia; Herry Purnama (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2021)
Activated carbon also known as activated charcoal is a common term for carbon materials, which comprises charcoal. Activated carbon has a good adsorption capacity against gases and pollutants in liquids because of its wide surface. The material used in this research was tropical black bamboo, with the variation of particle size -10+20 mesh, -20+40 mesh, -40+60 mesh and -60+80 mesh.  There are 2 processes to produce activated carbon, i.e. carbonation and activation. In this research, the carbonation is set at 380°C in 1 hour. Then, each size of carbon was activated by H3PO4 9.8% along 24 hours. The analysis conducted were moisture content, ash content, iodine number, and functional group analysis using Fourier Transform Infrared Spectroscopy (FTIR). The smaller particle size, the more pores will be produced and it caused the surface area higher. The results showed that variation of particle size had effect on the characterization and quality of activated carbon, where moisture content is between 10.60 to 4.05%, ash content is 1% to 0.2% and iodine adsorption is between 710 mg/g to 900 mg/g. In FTIR analysis, it showed that all of the samples had O-H, C=C, and C-O functional group.